New science, new world - Albanese, Denise (Duke University Press, 1996)
In New Science, New World Denise Albanese examines the discursive interconnections between two practices that emerged in the seventeenth century - modern science and colonialism. Drawing on the discourse analysis of Foucault, the ideology-critique of Marxist cultural studies, and de Certeau's assertion that the modern world produces itself through alterity, she argues that the beginnings of colonialism are intertwined in complex fashion with the ways in which the literary became the exotic "other" and undervalued opposite of the scientific